1994
DOI: 10.1111/j.1439-0396.1994.tb00392.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity of amylase in the gastrointestinal tract of the horse1

Abstract: Zusammenfassung Die Aktivität der Amylase im Magen‐Darm‐Kanal des Pferdes An insgesamt 18 Pferden (146–410 kg KM) wurde die Aktivität der Amylase im Pancreasgewebe (postmortal, n = 8), im Chymus des terminalen Jejunums (Fistel am Ende des Jejunums, n = 8) bzw. des Caecums (Caecumfistel, n = 2) nach Fütterung von Getreide (Hafer, Mais, Gerste in verschiedenen Zubereitungen), Maissilage und Corn‐Cob‐Mix sowie Knollenstärken (Tapioka, rohe Kartoffeln) im Vergleich zu ausschließlicher Heufütterung überprüft. Der E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 6 publications
0
34
0
4
Order By: Relevance
“…Also, in ponies feed with oats leads to increased blood glucose compared with the diets containing barley and corn (Vervuert and Coenen 2005). Because oats starch digestibility is more than corn and barley in prececal (Kienzle et al 1992;Potter et al 1992;Meyer et al 1995).…”
Section: Serum Biochemical Parametersmentioning
confidence: 99%
“…Also, in ponies feed with oats leads to increased blood glucose compared with the diets containing barley and corn (Vervuert and Coenen 2005). Because oats starch digestibility is more than corn and barley in prececal (Kienzle et al 1992;Potter et al 1992;Meyer et al 1995).…”
Section: Serum Biochemical Parametersmentioning
confidence: 99%
“…Feeding excessive amounts of starch can increase the risk of digestive and/or muscle problems. Total amylase secretion in the equine small intestine is considered to be a limiting factor for starch digestion (Kienzle et al 1994) and may result in an influx of readily fermentable carbohydrates (i.e. undigested starch) to the hindgut.…”
Section: Introductionmentioning
confidence: 99%
“…undigested starch) to the hindgut. This could result in colic due to excessive hindgut fermentation (Potter et al 1992a;Kienzle et al 1994) and an altered microbial activity, leading to unrestrained gas production and a reduction in hindgut pH (Beyer 1998). Also, gastric ulcers (Beyer 1998) and 'tying-up' (both sporadic and recurrent exertional rhabdomyolysis; Valberg 1998) may be related to excessive use of grains and sweet-feed in equine rations.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of this ingredient in the concentrate may foment a reduction in starch supply in horse meals, being the maximum suggested starch supply of 0.2% per meal (Kienzle et al, 1994). Little is known about the acceptability of this ingredient, being described only by Ott et al (1979), who found that diets with 30% inclusion of citrus pulp were not accepted by horses.…”
Section: Introductionmentioning
confidence: 99%